Integrated polarisation handling devices. Issue 3 (1st June 2020) - Saber, Md Ghulam; Xu, Luhua; Sagor, Rakibul Hasan; Wang, Yun; Kumar, Amar; Mao, Deng; El‐Fiky, Eslam; Patel, David; Samani, Alireza; Xing, Zhenping; Jacques, Maxime; D'Mello, Yannick; et al.
Abstract : Photonic integrated circuits (PICs) suffer from birefringence due to high‐index contrast. Polarisation handling devices improve the performance of the PICs by reducing the polarisation‐dependent dispersion and loss. Furthermore, there is a growing interest in building polarisation division multiplexed transceivers using PICs, which require polarisation management. The authors provide an overview of the recent work on developing polarisation handling devices such as polarisation beam splitters and polarisers in indium phosphide and silicon‐on‐insulator platforms for optical communications and sensing applications. These devices expand the PICs library of polarisation handling devices and can be used to design more complex circuits with advanced or new functionalities.